Testing the Effect of Bending Moment on Wheel Bearing Heating - Stancekova, Dana; Mrázik, Jozef; Ťavodová, Miroslava; Sapietová, Alžbeta; Rudawska, Anna; Turian, Filip (Manufacturing Technology Journal, 2022)
Leading manufacturers and sellers of products in the field of rolling bearings for the automotive in-dustry guarantee their quality. Extensive product testing is required to guarantee quality. When test-ing wheel bearings, bending fatigue test stations are used, among other things, to verify the strength of components. The content of the presented work is the analysis of the effect of bending moment on the temperature of a newly wound wheel bearing of the 3rd generation, based on experimental measurements. These are dynamic tests of the strength of wheel bearing components at a resonant test station. This verification is very important and has the effect of preventing the start of mass pro-duction of components that do not meet the basic safety requirements.
Keywords: bending moment; temperature; wheel bearing